Midgut Transcriptional Variation of Chilo suppressalis Larvae Induced by Feeding on the Dead-End Trap Plant, Vetiveria zizanioides - Lu, Yanhui; Zhao, Yanyan; Lu, Han; Bai, Qi; Yang, Yajun; Zheng, Xusong; Lu, Zhongxian (Frontiers in Physiology, 2018)
Chilo supprressalis is one of the most important rice pests that causes serious damage to production in the rice growth area of Asia. Vetiver grass (Vetiveria zizanioides) was previously found to effectively attract female adults of C. suppressalis laying eggs on vetiver leaves, while the larvae cannot complete their life cycles by feeding on vetiver, indicating a potential means of controlling this pest. In the present study, the transcriptomes of midguts of rice-fed and vetiver-fed C. suppressalis larvae were profiled, which aimed to clarify the molecular mechanism of vetiver as a dead-end trap plant preliminarily. We found that ingestion of vetiver provoked a robust transcriptional response in the larval midguts, and a total of 1,849 differentially expressed UniGenes were identified. We focused on 12 digestion-related genes, four immune-related genes and three detoxification-related genes. Most of these genes were significantly down regulated in the larval midguts at 6, 8 and 10 days after feeding on vetiver compared to on rice. Transcriptional dynamics suggested that these genes might be involved in toxicity responses following exposure to vetiver. Taken together, this study provides an initial molecular framework for developing biological control strategies for C. suppressalis in an effort to protect economically important rice crops.